Manipulating optical absorption and polarization using microwave control in an atomic vapor - A Tretiakov; C A Potts; B Lu; J P Davis; L J LeBlanc (JPhys Photonics, 2024)
The multiplicity of atomic states (and the transitions between them) offer an innate, coherent platform through which microwave and optical fields effectively interact. In an atomic vapor near room temperature, we combine optical and microwave fields to generate a macroscopic internal angular momentum among the atoms—an atomic polarization—at an arbitrary angle with respect to the optical (laser) beam. This geometric freedom enables microwave control over photonic degrees of freedom, which we use in two demonstrations: using microwave-assisted optical pumping, we can rotate linear polarization through several degrees, and we can control the absorption for specific transitions and polarizations, which has applications for microwave-to-optical transduction.